Sharing Cost of Shared Services Centre - Tomáš Buus (European Financial and Accounting Journal, 2011)
In the presented paper we develop model of apportionment of cost generated by variability and mean value of flows from (to) shared services centre. It can be either cash pool or distribution centre, or even some kind of customer service centre. The apportionment formula for the cost of capacity generated by flow variability turns out to be regression coefficient of flow to (from) the distribution centre (cash pool) generated by particular company within the multibusiness enterprise as endogenous variable to flow of inventory (cash) for the whole distribution centre (cash pool) as exogenous variable. The cost generated by the flow of requirements (goods, money) itself, i.e. by the mean value of the flow, has to be split between SSC customers according to their share on that flow. Result does not depend on the form of cost function as long as it is strictly increasing function of flow from (into) SSC (orders, stock, cash) and of mean of that flow.
Keywords: C61; G39; M21; 650; Distribution centre; Cash Pool; Capacity; Cost Attribution